APPLIED GEOSTATISTICS TO THE ASSESSMENT OF ENHANCED GEOTHERMAL SYSTEM (EGS) IN CENTRAL SUMATERA BASIN - Sihotang, Josua Washington; Alam, Syaiful (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2019)
Thick sediment (over 2,500 m), fractured basement and high thermal gradient (up to 19.10 C/100 m) of Central Sumatra Basin are suitable factors to have the Enhanced Geothermal System (EGS) potential. A number of 130 wells data were used to evaluate the EGS of the basin. The assessment is divided into the number of estimation within the grid cell (1x1 km) of sediment thickness, heat flow, thermal conductivity and technical potential calculated starting from basement-sediment layer interface. The distribution of heat flow and gradient thermal values correspond to the sediment layer. The autocorrelation test indicates the data is stationary. The variance of data gets bigger after a depth over 5.5 km. According to the Beardsmore protocol, the technical potential value ranged from 0.5 MW up to 4.7 MW at a depth of 3.5 km. In addition, the lowest technical potential is 0.66 MW and the highest is 5.76 MW at a depth of 4.5 km. The ordinary kriging, using the number of lags 10 in variogram modeling, estimated the technical potential distribution is higher to the southwest.